THE EFFECT OF CSR DISCLOSURE ON FIRM VALUE WITH PROFITABILITY AND LEVERAGE AS MODERATING VARIABLES - Dewa Gede Mahesa Pratama; I Wayan Gde Wahyu Purna Anggara (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on firm value, as well as to explore the moderating role of profitability and leverage. The research objects are energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. Firm value is measured using Tobin’s Q ratio, CSR disclosure is assessed using the GRI 2021 index, profitability is proxied by Return on Equity (ROE), and leverage by the Debt to Equity Ratio (DER). The analytical methods employed include moderated regression analysis (MRA) and residual tests, using secondary data obtained from annual and sustainability reports. This research is expected to provide a deeper understanding of the relationship between CSR disclosure and firm value, as well as the extent to which profitability and leverage moderate this relationship. The findings are also anticipated to offer theoretical contributions and practical implications for both management and investors.